Penetrating injury extending from oral cavity to the neck - with an indigenous weapon - Talukder, Debesh Chandra; Islam, MZ; Khan, MAS; Rahman, Atiar (Journal of Dhaka Medical College, 2013)
A penetrating injury that extends from oral cavity deep into the right side of the neck. It is a diagnostic and a therapeutic challenge to the treating surgeon, because a number of important structures are densely packed in a small area, and the injury to any of these structures may immediately cause a life threatening situation. We are describing an interesting case, where a 55- year old man presented with a penetrating neck injury which was caused by an indigenous weapon , which ran from the oral cavity to the right side of the neck, X ray revealed the elongated pointed tip foreign object ran through oral cavity to the level of the body of 7th cervical vertebrae. The patient was found to have stable vitals and no active bleeding from the wounds; exploration of the neck was done under General aneasthesia with endo tracheal intubation through tracheostomy opening . The weapon was dislodged from the bamboo made handle , and retrieved under direct vision. Surprisingly, there were no injuries to any vital structures of the neck. The patient made an uneventful recovery. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15690 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 87-89